Analisis Penggunaan Combine Harvester Terhadap Pendapatan Petani Dari Usahatani Padi Di Desa Lambunot Kecamatan Simpang Tiga Kabupaten Aceh Besar - Noufal Fadlul Rahman; Agustina Arida; Sofyan Sofyan (Jurnal Ilmiah Mahasiswa Pertanian, 2021)
Rice is one of the commodities as an ingredient to meet the basic needs of the community and as a source of income for farmers. Lambunot Village is one of the villages in Simpang Tiga Subdistrict, Aceh Besar Regency which in the last 2 years has switched to using a modern rice harvester combine harvester in the rice harvesting process. The advantages of using this tool are that it can reduce yield loss, reduce labor and agricultural tools, and shorten harvesting time, so that it is considered to increase the income of user farmers. This study aims to determine the ratio of income and to determine the largest cost component during one growing season in rice farming farmers using combine harvester machines with non-combine harvester farmers in Lambunot Village. The analytical technique used in this research is income analysis and t-test (Independent sample T Test). The results showed that the average net income per 1 ha of rice farming using combine harvester farmers was greater than the net income of non-combine harvester farmers, which was Rp. 12,502,572 compared to Rp. 9,646,198. The results of the t-test test also explain that there is a significant difference in net income between rice farming farmers using combine harvesters and rice farming farmers using non-combine harvesters. Then the largest cost component in rice farming for combine harvester farmers is the cost of harvesting or biaya combine harvester dengan biaya Rp. 2.778.718 atau 30,78% dari total biaya produksi, sedangkan komponen biaya terbesar pada usahatani padi non-combine harvester adalah biaya tenaga kerja atau biaya sebesar Rp. 3.246.344 atau 31,48% dari total biaya produksi. Dapat disimpulkan bahwa penggunaan combine harvester rice harvester sangat layak untuk digunakan petani di kemudian hari karena terbukti mampu memangkas biaya produksi dan mengurangi kerugian sehingga meningkatkan pendapatan petani pengguna.